From policy to practice: Inclusion, exclusion, and the gendered realities of school re-entry programme for teenage mothers in Tanzania - Nalailaa, Stephano; Massawe, Hanifa (INTERNATIONAL JOURNAL OF ADOLESCENCE AND YOUTH, 2026)
This study explored teenage mothers' narratives on challenges and resilience in alternative secondary education pathways (ASEP). ASEP refers to flexible secondary-level education arrangements delivered through dedicated centres that offer modular and non-formal pathways for learners who are unable to attend mainstream schools, including teenage mothers. The study employed a qualitative perspective, integrating attachment, identity, self-efficacy, and critical race theory. It involved seventy (70) teenage mothers from purposively selected ASEP centres in Morogoro, Mwanza, Mara and Singida, using interviews, questionnaires and documentary reviews. The study revealed that most teenage mothers felt that parenthood strengthened their schooling commitment but faced stigma and self-doubt due to parenting duties. Some legal and systemic barriers limit educational participation, predicting further exclusion from sustainable economic growth. Recommendations push for flexible schedules, modular curricula, and alternative learning pathways to accommodate teenage mothers' parenting responsibilities, and data-driven frameworks for monitoring ASEP's.